ADVANCED MONITORING AND INTELLIGENT CONTROL FOR DYNAMIC COOLING STRATEGIES IN SOLAR SYSTEMS (CIPEEX, 2024)
THIS RESEARCH DELVES INTO THE DEVELOPMENT OF ADVANCED MONITORING SYSTEMS AND CONTROL ALGORITHMS DESIGNED TO DYNAMICALLY ADJUST COOLING STRATEGIES BASED ON ENVIRONMENTAL AND LOAD CONDITIONS IN SOLAR INSTALLATIONS. THE INTEGRATION OF REAL-TIME MONITORING AND INTELLIGENT CONTROL MECHANISMS IS PIVOTAL FOR OPTIMIZING THE PERFORMANCE, ENERGY EFFICIENCY, AND SUSTAINABILITY OF SOLAR SYSTEMS. FOR INSTANCE, THE IMPLEMENTATION OF SMART SENSORS CAN CONTINUOUSLY ASSESS AMBIENT TEMPERATURE, SOLAR IRRADIANCE, AND SYSTEM LOAD. THESE DATA POINTS ARE THEN PROCESSED BY ADAPTIVE CONTROL ALGORITHMS, WHICH DETERMINE THE MOST EFFECTIVE COOLING STRATEGY IN RESPONSE TO CHANGING CONDITIONS. A PRIME EXAMPLE IS THE USE OF MACHINE LEARNING ALGORITHMS THAT ANALYZE HISTORICAL DATA TO PREDICT TEMPERATURE FLUCTUATIONS AND ADJUST COOLING MECHANISMS ACCORDINGLY. MOREOVER, THIS RESEARCH EXPLORES THE POTENTIAL OF CLOUD-BASED MONITORING PLATFORMS, WHICH ENABLE REMOTE MONITORING AND CONTROL OF SOLAR INSTALLATIONS, ENSURING OPTIMAL OPERATION EVEN IN DIVERSE GEOGRAPHICAL LOCATIONS. THE SEAMLESS INTEGRATION OF THESE MONITORING AND CONTROL SOLUTIONS PROMOTES THE LONG-TERM RELIABILITY OF SOLAR SYSTEMS WHILE MAXIMIZING ENERGY YIELD. ULTIMATELY, BY FOSTERING ADAPTABILITY AND RESPONSIVENESS TO ENVIRONMENTAL AND LOAD VARIATIONS, THIS RESEARCH CONTRIBUTES TO THE ADVANCEMENT OF SUSTAINABLE AND EFFICIENT SOLAR ENERGY SOLUTIONS.
Keywords: Advanced Monitoring; Cooling Systems; Energy Efficiency; Photovoltaic